Perbandingan Hukum Peradilan Tata Usaha Negara Dan Verwaltungsgericht Sebagai Bentuk Perlindungan Hukum Kepada Rakyat - HABIBI, DANI (Jurnal Hukum & Pembangunan, 2019)
Legal issues that will be discussed in this paper regarding the description of the Administrative Court system in Germany and the Administrative Court system in Indonesia. Generally, there are similarities between the Administrative Court system in Germany and the Administrative Court system in Indonesia. The system can be seen from the level of the justice system starting from the first level, the level of appeal and the final level or cassation. In addition, it will be reviewed in relation to the judicial process, the basics of the lawsuit filed against the government and the way in which the state administrative court processes are carried out in each country. The research method is normative legal research with the approach of legislation and legal comparison.